Sinergi Mahasiswa dan Masyarakat dalam Mewujudkan Desa Mandiri Budaya dan Sadar Hukum di Padukuhan Tangisan - Tias Anggrayani; Yelia Defrianti; Disraely Ivan Hamel Walalangi; Ferdinan Dicky Kurniawan; Rodhi Aji Wibowo; Liliosa Astuti; Angger Tirandana; Suhardiman Abdus Syukur; Gerend Dody Husni Pratama; Didi Setiawan (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The 2025 Thematic Community Service Program (KKN-T) for the R3 group of Janabadra University Yogyakarta was held in Tangisan Hamlet, Banyurejo Village, Tempel Subdistrict, Sleman Regency. Tangisan Hamlet has various local potentials that can be developed, such as a productive agricultural sector, active social institutions, and a rich cultural heritage. However, this area also faces several challenges that need to be addressed, including low legal literacy among the community, a high potential for juvenile delinquency, and limited public information support facilities in the hamlet. In implementing the KKN-T program, a participatory approach was applied by involving the local community from the planning stage to the evaluation. The process began with field observations to understand the actual conditions in the community, then continued with the formulation of a work program developed in collaboration with community leaders and village officials. The programs implemented included the installation of information signs in Javanese script at strategic points as part of supporting the "Culturally Independent Village" program. In addition, socialization was conducted regarding laws related to online loans and juvenile delinquency, which aimed to increase public understanding of legal issues. At Banyurejo 4 Public Elementary School, anti-bullying education is being conducted to raise students' awareness of the importance of mutual respect. Furthermore, at the Integrated Service Post (Posyandu) for toddlers, nutritious supplementary food using local foods is provided to support children's health in the area. All implemented programs are based on the actual needs of the community, identified through discussions and deliberations with community leaders. Through this Community Service Program (KKN-T) activity, it is hoped that a strong synergy will be established between students, the community, and the village government in promoting sustainable and independent village development. This program is expected to provide direct benefits to the community and pave the way for better village development in the future.